2021
DOI: 10.1186/s13049-021-00878-2
|View full text |Cite
|
Sign up to set email alerts
|

Do team and task performance improve after training situation awareness? A randomized controlled study of interprofessional intensive care teams

Abstract: Background When working in complex environments with critically ill patients, team performance is influenced by situation awareness in teams. Moreover, improved situation awareness in the teams will probably improve team and task performance. The aim of this study is to evaluate an educational programme on situation awareness for interprofessional teams at the intensive care units using team and task performance as outcomes. Method Twenty interprof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 46 publications
1
18
0
2
Order By: Relevance
“…Nevertheless, Emani et al [ 60 ] and Jafri et al [ 74 ] show a correlation between TS scores and HFS scores, which emphasises that the effect of SBT is evident when HFS is trained solely in combination with other competencies. Studies of multi-disciplinary training ( n = 47) [ 13 , 48 , 53 , 56 , 58 64 , 66 – 69 , 71 – 102 ] were generally associated with greater effectiveness than mono-disciplinary training, perhaps because multi-disciplinary training better reflects everyday clinical practice.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, Emani et al [ 60 ] and Jafri et al [ 74 ] show a correlation between TS scores and HFS scores, which emphasises that the effect of SBT is evident when HFS is trained solely in combination with other competencies. Studies of multi-disciplinary training ( n = 47) [ 13 , 48 , 53 , 56 , 58 64 , 66 – 69 , 71 – 102 ] were generally associated with greater effectiveness than mono-disciplinary training, perhaps because multi-disciplinary training better reflects everyday clinical practice.…”
Section: Resultsmentioning
confidence: 99%
“…There are inherent challenges in using rating and self-assessments because assessors must be congruent and unbiased, and participants tend to overrate their performance and therefore, the method has been proven unreliable [ 123 , 124 ]. Some studies ( n = 21) used video recording and blinded assessors [ 47 , 48 , 54 , 58 , 60 , 61 , 63 , 66 , 70 , 71 , 74 , 76 , 89 , 91 , 98 , 99 , 103 , 106 , 108 , 111 , 114 ], which increased the validity of the ratings; because the assessors’ could rewind the video and review the situation multiple times. Other studies rated participants in real-time, which challenged the assessors’ ability to simultaneously watch, listen and rate [ 10 , 49 51 , 53 , 57 , 59 , 62 65 , 67 , 68 , 72 , 73 , 75 , 77 79 , 81 , 85 , 93 , 96 , 101 , 107 , 115 , 125 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven of these studies employed an observational design [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. One was a randomized controlled intervention [ 18 ]. The results of this review showed that the term “shared situational awareness” in itself was not commonly used; instead “team situational awareness” was the most commonly used term [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although, SSA is not globally used in the hospital emergency context [ 19 ], the review results revealed that Endsley’s frameworks [ 2 ] were the most used SA frameworks in the hospital emergency context. Four studies [ 11 , 12 , 15 , 18 ] employed the three-levels of Endsley’s framework [ 2 ], while one study has used one level of the framework [ 13 ]. According to Endsley’s framework [ 2 ], situational awareness components are Level 1: perception of the information present in the situation, Level 2: comprehension of what the information present in the situation means and, Level 3: projection of what might happen in the situation in the near future.…”
Section: Resultsmentioning
confidence: 99%